2006
DOI: 10.1007/s10815-006-9021-9
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding epidermal growth factor (HB-EGF) may improve embryonic development and implantation by increasing vitronectin receptor (integrin ανβ3) expression in peri-implantation mouse embryos

Abstract: HB-EGF may improve implantation by accelerating expression of integrin alphanubeta3 in peri-implantation mouse embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
4
24
0
Order By: Relevance
“…HBEGF signaling is required to increase HBEGF protein levels when O 2 is decreased to 2% [18], and both immunohistochemical and ELISA data indicated that HBEGF upregulation can be mediated by any one of the three MAPK pathways. These data confirm prior reports that HBEGF inhibits apoptosis [18,19,24,43] and promotes differentiation of trophoblast cells toward a migratory, extravillous phenotype [15,17,44]. Moreover, the new findings identify separate downstream signaling pathways mediated by HBEGF-induced ERBB/HER activation that are responsible for each functional outcome.…”
Section: Discussionsupporting
confidence: 89%
“…HBEGF signaling is required to increase HBEGF protein levels when O 2 is decreased to 2% [18], and both immunohistochemical and ELISA data indicated that HBEGF upregulation can be mediated by any one of the three MAPK pathways. These data confirm prior reports that HBEGF inhibits apoptosis [18,19,24,43] and promotes differentiation of trophoblast cells toward a migratory, extravillous phenotype [15,17,44]. Moreover, the new findings identify separate downstream signaling pathways mediated by HBEGF-induced ERBB/HER activation that are responsible for each functional outcome.…”
Section: Discussionsupporting
confidence: 89%
“…EGF (Desai et al 2000) and HB-EGF (Martin et al 1998;Lim et al 2006) have also been reported to stimulate the proportion of hatching blastocysts in several mammalian species. The mechanisms by which growth factors promote the formation of hatching blastocysts are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Culture media supplemented with various growth factors have been used to study their possible effect on in vitro development. A number of studies have reported that for in vitro culture of preimplantation embryos, the addition of exogenous growth factors, including the epidermal growth factor (EGF) family, the insulin and insulin-like family of growth factors, the transforming growth factor-β (TGF-β) family, the platelet-derived growth factor and fibroblast growth factor family, could affect the preimplantation development and result in a broad range of effects that include stimulation of protein synthesis in mice (Wood and Kaye 1989) and pigs (Lewis et al 1992), promotion of blastocyst formation in cattle (Larson et al 1992;Yang et al 1993;Lima et al 2006) and mice (Paria and Dey 1990), increasing the percentage of hatching blastocysts in mice (Lim et al 2006) and humans (Martin et al 1998), increase in the number cells in blastocysts in mice (Lin et al 2003) and cattle (Sirisathien et al 2003), and prevention of apoptosis in rabbits (Herrler et al 1998) and human (Spanos et al 2000).Clearly a better understanding of the role of growth factors in development could help to elucidate the mechanisms controlling embryonic development and to improve the viability and development of embryos in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, it has been well established that endometrial integrins are hormonedependent (Lessey, 1995) and participate in multiple reproductive events including fertilization, implantation and placentation in various species (Bowen and Hunt, 2000). Some factors known to be involved in the implantation process, such as IGF-1 (Kabir-Salmani et al, 2004), CCN1 (Winterhager and Gellhaus, 2014) and HB-EGF (Lim et al, 2006), may act through interaction with integrins. Of the integrin members, the αVβ3 Figure 3 (A) Relative luciferase activity in HEK293T cells co-transfected with miR-126a-3p mimics, inhibitor and the wide-type (wt-) or mutant (mu-) Itga11 vectors.…”
Section: Article In Pressmentioning
confidence: 99%